Downfall - Oliver, Hirschbiegel; Bruno, Ganz.; Alexandra Maria Lara; Corinna Harfouch; Ulrich Matthes; Juliane Köhler (Sony Pictures USA, 2005)
The riveting subject of Downfall is nothing less than the disintegration of Adolf Hitler in mind, body, and soul. A 2005 Academy Award nominee for best foreign language film, this German historical drama stars Bruno Ganz (Wings of Desire) as Hitler, whose psychic meltdown is depicted in sobering detail, suggesting a fallen, pathetic dictator on the verge on insanity, resorting to suicide (along with Eva Braun and Joseph and Magda Goebbels) as his Nazi empire burns amidst chaos in mid-1945. While staging most of the film in the claustrophobic bunker where Hitler spent his final days, director Oliver Hirschbiegel (Das Experiment) dares to show the gentler human side of der Fuehrer, as opposed to the pure embodiment of evil so familiar from many other Nazi-era dramas. This balanced portrayal does not inspire sympathy, however: We simply see the complexity of Hitler's character in the greater context of his inevitable downfall, and a more realistic (and therefore more horrifying) biographical portrait of madness on both epic and intimate scales. By ending with a chilling clip from the 2002 documentary Blind Spot: Hitler's Secretary, this unforgettable film gains another dimension of sobering authenticity.
Languages : Turkish, German Subtitles : English, Turkish, German
Keywords: War; Drama; Art House and International